#1**+2 **

Note that 4x^2 -1 = (2x-1)(2x+1) multiply BOTH sides of the equation by this to get

2x+1 + 2x-1 + 7 = 4x^2 -1 simplify

4x + 7 = 4x^2 -1

4x^2-4x-8 = 0 Quadratic Formula yields x = 2 or -1

ElectricPavlov Jun 9, 2020

#2**+5 **

Your not wrong when you say this is hard...

I'll take a shot at it...

I got the values x = 2

and x = -1

They seem to work...

I first factored 4x^2 - 1 to get (2x + 1)(2x - 1). When we add fractions we multiply the denominators to get the common denominator.

When I factored 4x^2 - 1 I got (2x + 1)(2x - 1) and that is the same denominator when you multiply the other 2 denominators together.

We get 4x/(2x + 1)(2x - 1)

We multiply 1 by (2x + 1)(2x - 1) so the denominator cancels out.

We get 4x + 7 = (2x + 1)(2x - 1)

We expand (2x + 1)(2x - 1) to get 4x^2 - 1.

4x + 7 = 4x^2 - 1

We subract 7 on both sides to receive 4x^2 - 8 = 4x

Then, we subtract 4x from both sides to get 4x^2 - 8 - 4x = 0

We can use the quadratic formula to find the solution from here on out.

a = 4, b = -4, c = -8

\(x = {-4 + \sqrt{(-4)^2-4(4(-8)} \over 2(4)}\)

Saving you time, this gives us 2 and -1.

Forgo Jun 9, 2020